PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN AUGMENTED REALITY (AR) DENGAN SOFTWARE PAINT 3D BAGI GURU MATEMATIKA SMP - Nurcahyo, Adi; Ishartono, Naufal; Waluyo, Mohamad; Sutama, Sutama; Sari, Fhitri Indah (Jurnal Terapan Abdimas, 2022)
Abstract. Augmented Reality (AR) is a technology for implementing 3D objects in real life. 3D objects help students to visualize abstract objects in mathematics so that they are easy to understand. Abstract objects in mathematics that require visualization include geometric material. Software that is easy to use and has a size that is not too large to help visualize abstract objects by creating 3D objects that are Paint 3D. The purpose of the training activities is to improve the competence of mathematics teachers in making learning media with 3D objects. The media created can be a means for teachers to provide understanding for students about geometry material. The target of the training was the mathematics teachers of Muhammadiyah junior high school in Gemolong. The training method used has several stages including problem analysis, preparation, implementation, evaluation, and publication. At the stage of implementing the training using participatory training methods, participants can practice and ask questions related to the obstacles experienced. The results of the training carried out include mathematics teachers who can create learning media in the form of 3D objects and implement them in learning. The results of the post-test of the training activities, 86% of participants clearly understood the delivery of the material presented by the presenters, 94% of the training participants were satisfied with the training activities held. 89% of participants are able to create 3D objects using Paint 3D software based on the delivery given by the presenters and 80% of participants will implement 3D objects in learning.  Abstrak. Augmented Reality (AR) merupakan teknologi untuk mengimplementasikan objek 3D dalam kehidupan secara nyata. Objek 3D membantu siswa untuk memvisualisasikan objek-objek abstrak dalam matematika sehingga mudah dipahami. Objek abstrak dalam matematika yang membutuhkan visualisasi diantaranya terdapat pada materi geometri. Software yang mudah digunakan dan memiliki ukuran tidak terlalu besar untuk membantu memvisualisasi objek abstrak dengan membuat objek 3D yaitu Paint 3D. Tujuan dari kegiatan pelatihan untuk meningkatkan kompetensi guru-guru matematika dalam membuat media pembelajaran dengan objek 3D. Media yang dibuat dapat menjadi sarana bagi guru untuk memberikan pemahaman bagi siswa tentang materi geometri. Target dari pelatihan yang dilakukan yaitu guru-guru matematika SMP Muhammdiyah di Gemolong. Metode pelatihan yang digunakan memiliki beberapa tahapan diantaranya analisis permasalahan, persiapan, pelaksanaan, evaluasi, dan publikasi. Pada tahapan pelaksanaan pelatihan menggunakan metode pelatihan partisipatif dengan peserta dapat mempraktekkan dan bertanya terkait kendala yang dialami. Hasil pelatihan yang dilakukan diantaranya guru-guru matematika dapat membuat media pembelajaran berupa objek 3D dan mengimplementasikan dalam pembelajaran. Hasil post-test kegiatan pelatihan yaitu sebanyak 86% peserta memahami dengan jelas penyampaian materi yang disampaikan oleh pemateri, sebanyak 94% peserta pelatihan merasa puas dengan kegiatan pelatihan yang diadakan. Sebanyak 89% peserta mampu untuk membuat objek 3D menggunakan software Paint 3D berdasarkan penyampaian yang diberikan pemateri dan 80% peserta akan mengimplementasikan objek 3D dalam pembelajaran.